1994
DOI: 10.3109/02699059409151024
|View full text |Cite
|
Sign up to set email alerts
|

Late outcome of mild head injury: Results from a controlled postal survey

Abstract: There is insufficient information about the long-term sequelae of mild head injury (postconcussional symptoms, PCS). Therefore, a questionnaire-based investigation was carried out in patients 1-5 years after mild head injury (MHI) and in non-concussed subjects in order to study the nature of long-term complaints after MHI. A three-factor model of residual subjective and psychological complaints that contained a dysthymic factor, a vegetative/bodily complaints factor, and a cognitive performance factor were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 12 publications
2
28
0
Order By: Relevance
“…Researchers have reported post-concussion symptoms in trauma patients who are 1 or more years post-injury [35][36][37]; however, the underlying causes of these persistent, long-term symptoms are subject to considerable debate. Moreover, a carefully controlled, large-scale, prospective study of trauma patients with uncomplicated mild traumatic brain injuries demonstrated that long-term post-concussion symptoms were rare [38].…”
Section: Discussionmentioning
confidence: 98%
“…Researchers have reported post-concussion symptoms in trauma patients who are 1 or more years post-injury [35][36][37]; however, the underlying causes of these persistent, long-term symptoms are subject to considerable debate. Moreover, a carefully controlled, large-scale, prospective study of trauma patients with uncomplicated mild traumatic brain injuries demonstrated that long-term post-concussion symptoms were rare [38].…”
Section: Discussionmentioning
confidence: 98%
“…In addition, similar percentages (of 12 time points) were calculated for the four distinct time periods (morning, midday afternoon, evening). 4. Emotional distress, personality, physical functioning, and fatigue.…”
Section: Data Collectionmentioning
confidence: 99%
“…Although most MTBI patients recover well, a minority reports cognitive difficulties for months to years after injury [2][3][4][5]. These complaints are distressing, may lead to a disabled lifestyle, and prolong medical consumption [6,7].…”
Section: Introductionmentioning
confidence: 98%
“…To account for spontaneous resolution of symptoms, persistence of symptoms for more than 3 months is commonly used as a diagnostic criterion, even though earlier diagnosis would be desirable [American Psychiatric Association, 1994]. Additionally, many confounding factors for the development of postconcussion syndrome have been identified, such as litigation, psychological distress or anxiety due to the traumatic event, premorbid levels of complaints, and female gender [Alexander, 1997;Bazarian et al, 1999;Bohnen et al, 1994;King, 2003]. At an individual level, the use of cognitive fMRI may make early and reliable diagnosis possible and facilitate the identification of patients suitable for therapeutic intervention.…”
Section: Discussionmentioning
confidence: 99%